FROM DNA TO CHROMOSOME: A VIEW OF BISCUIT PACKAGING - Campos, Maria Rita de Cássia (Seven Editora, 2025)
The development of didactic models in the teaching of abstract concepts is proposed, since it allows the assimilation of content in an expanded and three-dimensional view. The present work aimed to develop three-dimensional models in biscuits addressing the packaging of chromatin into chromosomes from DNA. This work presents a qualitative approach research. The activities were developed by students of the 1st period of the Bachelor's Degree in Biological Sciences at the Federal University of Catalão, regularly enrolled in the Cell Biology discipline. Initially, the students participated in a workshop, provided by the teacher, and chose the references that supported (conceptually and pedagogically) the model to be produced and the material to be used. Then, the model was made during part of the practical classes. The proposal instigated the interest of the students. The act of choosing nuclei, position, proportionality and application in the model stimulated interest and curiosity, enabling different ways of learning the compaction of chromatin into chromosomes. I suggest that cookie modeling, with the student as the learning center, be the subject of other biology topics.DOI: https://doi.org/10.56238/sevened2024.037-172